Utilizing learning factory as enabler to TVET goals: Students’ learning experience - Mohd Ghazali, Maarof; Muhammad Zam Zahari, Bohari (S, 2023)
One of the practical means of attaining sustainable development is Learning Factory (LF). Learners in Higher Education Institutions (HEIs) can build their essential competencies in a real-world setting within the LF setting. This article's goal is to examine the value of LF in HEIs and the suggested expansion of LF in HEIs to achieve TVET goals. One issue facing industry around the world is a lack of skilled workers to meet emerging industry requirements. This issue requires the educational content and didactical methodologies improvement. However, many universities are not applying teaching and training techniques that ready students for industrial employment. The learning factory concept can be introduced to the institution as a means of resolving this problem. This is because the learning factory technique incorporates business activities into the educational process. This study examines the advantages of applying the learning factory concepts based on a Malaysian public university experience. Open-ended questions were given to 63 students who had used the learning factory. This study revealed three key advantages, including increased learning process interest, student hands-on experience based on genuine industrial job life, and improved lecturer to student knowledge transfer. Findings from this study can assist instructors, lecturers, or higher education institution management in coming up with new ways to make the process of imparting knowledge to students easier and more engaging, and at the same time supporting sustainable development goals. Future research may investigate the connection between teaching techniques and their academic success.